The TRIPS Project. - Burger, Doug; Keckler, Stephen W.; McKinley, Kathryn S. (Communications of the ACM, 2025)
The article discusses the TeraOp, Reliable, Intelligently Adaptive Processing System (TRIPS) research project at the University of Texas at Austin, and it mentions research funding from the U.S. National Science Foundation and federal government agencies, as well as information about research involving computer processor architectures and high-performance computer design. The U.S. Defense Advanced Research Projects Agency (DARPA) and explicit data graph execution are assessed.